2022
DOI: 10.1007/s10803-022-05795-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Moral Judgments in Impersonal and Personal Dilemmas in Autistic Spectrum Disorders from Childhood to Late Adolescence

Abstract: A potential underlying mechanism associated with the difficulties in social interactions in Autistic Spectrum Disorders (ASD) concerns the abnormal development of moral reasoning. The present study examined utilitarian and deontological judgments in impersonal and personal moral dilemmas, comparing 66 individuals with ASD and 61 typically developing (TD) individuals between 6 and 18 years. Utilitarian judgments decreased with age. This decline was much more gradual for personal dilemmas in the ASD than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Clarkson et al (2023), however, highlighted the impact of the degree of autism on moral decision-making, reporting atypical patterns of moral judgement to be exhibited by individuals with higher levels of autistic traits. Labusch et al (2024) reported that while autistic individuals endorsed the propriety of utilitarian judgements more than NTs, they felt less calm, suggesting a complex cognitive and emotional interplay involved in the moral judgements of autistic individuals. There was further complexity indicated by age-related changes in moral decision-making, which were found in both autistic and NT individuals, albeit found to be more gradual in the autistic group.…”
Section: Individual Differences Heterogeneity and Complexity Of Autis...mentioning
confidence: 99%
“…Clarkson et al (2023), however, highlighted the impact of the degree of autism on moral decision-making, reporting atypical patterns of moral judgement to be exhibited by individuals with higher levels of autistic traits. Labusch et al (2024) reported that while autistic individuals endorsed the propriety of utilitarian judgements more than NTs, they felt less calm, suggesting a complex cognitive and emotional interplay involved in the moral judgements of autistic individuals. There was further complexity indicated by age-related changes in moral decision-making, which were found in both autistic and NT individuals, albeit found to be more gradual in the autistic group.…”
Section: Individual Differences Heterogeneity and Complexity Of Autis...mentioning
confidence: 99%